1968
DOI: 10.1099/0022-1317-3-1-103
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Phage to Group N Streptococci. The Specificity of Adsorption and the Location of Phage Receptor Substances in Cell-wall and Plasma-membrane Fractions

Abstract: SUMMARYThe specificities of adsorption and multiplication of phages attacking some strains of lactic streptococci (serological group N) were investigated. At multiplicities of infection (m.o.i.) of o. I to I p.f.u./coccus, the specificity of adsorption was similar to that of multiplication, but some strains also adsorbed one or more h¢terotogous phages. At m.o.i. ~ IOO both homologous and heterologous strains of streptococci were lysed from without. The specificity of adsorption to cell walls was the same as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…They believe that some membrane sites may protrude through the wall and act as receptors for Strep. lactis bacteriophage, which Oram and Reiter (1968) found adsorbs to the membrane. This would be analogous to the plasma-membrane bridges described by Bayer (1968).…”
Section: B Surface Structures Of Gram-positive Bacteriamentioning
confidence: 99%
“…They believe that some membrane sites may protrude through the wall and act as receptors for Strep. lactis bacteriophage, which Oram and Reiter (1968) found adsorbs to the membrane. This would be analogous to the plasma-membrane bridges described by Bayer (1968).…”
Section: B Surface Structures Of Gram-positive Bacteriamentioning
confidence: 99%
“…This suggestion was based on an electron microscopic study of the surface of lactococci, which showed the plasma membrane protruding through holes in the cell wall (23), and the discovery of a phage-inactivating substance in the plasma membrane fraction of Lactococcus lactis subsp. lactis ML3 (32,33).Our laboratory has characterized phage receptors on the surface of two strains of L. lactis (44,46 …”
mentioning
confidence: 99%
“…On the other hand, the phage receptor material of grampositive bacteria, such as Staphylococcus aureus [14], Streptococci [12], Bacillus subtills [17], have been investigated and, in S. aureus and B. subtilis, it was shown that the cell wall teichoic acid [3,8] or some moiety of the teichoic acid [2,15] was essential for phage adsorption. The study of the phage receptor material of Lactobacillus casei was undertaken because L. casei has no teichoic acid in its cell wall and little is known about its phage receptor material.…”
mentioning
confidence: 99%